1976
DOI: 10.1029/jb081i017p02990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar activity on annual means of geomagnetic components

Abstract: Fourier analyses were made of the geomagnetic horizontal annual means from 20 observatories and the vertical component annual means from 17 observatories from 1900 to 1972 for most of the observatories. Curves synthesized from the Fourier coefficients for periods from approximately 4 to 13 yr have patterns easily explained in terms of a westward-flowing ring current that generally increases as the sunspot numbers increase but lags behind the sunspot numbers by a year or two. External spherical harmonic coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

1976
1976
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…We confirmed the well known presence in the annual means of geomagnetic elements of a 11-year solar-cyclerelated (SC) signal due to incomplete averaging out external effects and their induced counterparts, modulated by solar activity (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011) and quantitatively showed that the time change of the signal is of the same order of magnitude as that of the internal ingredients of the measured field. As a consequence, the SC signal should be filtered out before any discussion on SV.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We confirmed the well known presence in the annual means of geomagnetic elements of a 11-year solar-cyclerelated (SC) signal due to incomplete averaging out external effects and their induced counterparts, modulated by solar activity (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011) and quantitatively showed that the time change of the signal is of the same order of magnitude as that of the internal ingredients of the measured field. As a consequence, the SC signal should be filtered out before any discussion on SV.…”
Section: Discussionsupporting
confidence: 66%
“…Alexandrescu et al, 1995), but, we think, with increased possibilities for external effects to leak into the models. The presence in annual mean data of a solar-cycle-related (SC) signal due to incomplete averaging out of external effects, modulated by the solar activity, has long been recognized (Chapman and Bartels, 1940;Yukutake, 1965;Bhargava and Yacob, 1969;Alldredge, 1975Alldredge, , 1976Courtillot and Le Mouël, 1976;Alldredge et al, 1979;Yukutake and Cain, 1979;Demetrescu et al, 1988;Verbanac et al, 2007;Wardinski and Holme, 2011). Because at the observing point these effects comprise both the direct and the induced fields, and having in view the frequency difference of the SC variation in comparison to the secular variation, a suitable filter applied to data would eliminate both the external fields and their induced effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, YUKUTAKE (1965), ALLDREDGE (1976), RIVEN (1976), COURTILLOT andLE MOUEL (1976), andHAR WOOD andMALIN (1977) have found that values of the first degree external coefficients vary consistently with the solar cycle. In all of these analyses, when the solar cycle effect was being investigated, the data were first filtered to retain only those variations with periods near the solar cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The data from several dozen observatories had been used in analyses of the secular variations by many authors, e.g. YUKUTAKE (1965), BHARGAVA and YACOB (1969), CURRIE (1973), RIVIN (1974), ALLDREDGE (1976ALLDREDGE ( ,1977, COURILLOT and MODEL (1976), SRIVASTAVA and AB-BAS (1977). However they did not use the data of Hong Kong, except RIVIN's article (1974).…”
mentioning
confidence: 99%
“…The absence of a solar cycle (10-11 years) is important for the analysis, which will be discussed in a later paragraph. In order to compare the phase relation of these signals with the sunspot numbers, this paper used the method similar to ALLDREDGE (1976). The residual values were fit by a sum of trigonometric sine terms, the data being treated as an odd function with a fundamental period twice that of the observed interval.…”
mentioning
confidence: 99%